From Indifference to Entrapment The Netherlands and the Yugoslav Crisis, 1990-1995 - Both, Norbert (Amsterdam University Press, 2000)
A detailed analysis of the response to the Yugoslav crisis by one of America's key allies in NATO. The author focuses on the question of how a Western bureaucracy faced up to the most complex foreign policy challenge of the 1990s. The Netherlands, as a 'pocket-sized medium power', is an interesting case study. While the margins for Dutch foreign policy are limited, fate had it that the Netherlands occupied the European presidency during the second half of 1991, when the recognition issue divided the West and the parameters for the subsequent international intervention in the Balkans were set. By July 1995, the involvement of the Netherlands had deepened to the extent that Dutch troops who found themselves trapped in the UN safe area of Srebrenica together with the local Muslim population were unable to prevent the worst massacre in Europe since the Second World War. This study is based on interviews with all the major players, including two former Defence Ministers and two former Ministers of Foreign Affairs, and on documents from the Netherlands Ministry of Foreign Affairs, made available under the country's own 'freedom of information act'. This title is available in the OAPEN Library - http://www.oapen.org.